The "ABC" of Virus‐Specific T Cell Immunity in Solid Organ Transplantation. Issue 6 (25th February 2016) - Sester, M.; Leboeuf, C.; Schmidt, T.; Hirsch, H. H.
Abstract : Transplant patients are at increased risk of viral complications due to impaired control of viral replication, resulting from HLA mismatching between graft and host and the immunosuppression needed to avert alloimmune reactions. In the past decade, quantitative viral load measurements have become widely available to identify patients at risk and to inform treatment decisions with respect to immunosuppressive drugs and antiviral therapies. Because viral loads are viewed as the result of viral replication and virus‐specific immune control, virus‐specific T cell monitoring has been explored to optimize management of adenovirus, BK polyomavirus and cytomegalovirus ("ABC") in transplant patients. Although most studies are descriptive using different technologies, the overall results show that the quantity and quality of virus‐specific T cells inversely correlate with viral replication, whereby strong cellular immune responses are associated with containment of viral replication. The key obstacles to the introduction of assays for virus‐specific T cells into clinical practice is the definition of reliable cutoffs for clinical decision making, the poor negative predictive value of some assays, and the absence of interventional trials justifying changes of antiviral treatment or immunosuppression. More clinical research is needed using optimized assays and targets before standardization and commutability can be envisaged as achieved for viral load testing. Abstract : This minireview summarizes current state‐of‐the‐art virus‐specific T cell responses, including assay principles, their role in controlling viral replication, and areas for clinical use in transplant patients.